PEDAGOGICAL APPROACHES IN TEACHING MANDARIN FOR FIRST-YEAR STUDENTS OF APPLIED MANDARIN LANGUAGE BACHELOR PROGRAM AT UNIVERSITAS PRIMA INDONESIA - Siregar, Feby Yoana; Jessica; Purba, Wanda Angelia Fenensia; Syahputra, Fikry Prastya (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2025)
This study aims to examine the pedagogical approaches used in teaching Mandarin to first-year students of the Mandarin Applied Bachelor Program at Universitas Prima Indonesia. The research method used is descriptive qualitative through classroom observation and interviews with teachers and students. The main focus of this study is to identify the learning methods applied, assess their effectiveness, and understand the challenges faced in the process of mastering the four language skills: listening (听 tīng), speaking (说 shuō), reading (读 dú), and writing (写 xiě). The results of the study indicate that the pedagogical approaches used include Communicative Language Teaching (CLT), scaffolding, direct method, audio-lingual, and grammar translation method. These approaches encourage active student involvement, improve understanding of language concepts, and create a communicative and collaborative learning environment. Several challenges are still found, such as the lack of variation in learning media, less conducive learning time, and differences in student motivation levels. This study suggests the integration of interactive digital media and project-based learning approaches as solutions. The novelty of this study lies in the reflective integration of classical pedagogical approaches with the practical needs of business communication in the global era, as well as the direct mapping between learning time, student sitting position, and level of learning enthusiasm, which have not been widely explored in the local context of Mandarin learning in Indonesia.